The effect of cargo handling process at KLAS / Noradlina Satari - Satari, Noradlina (Faculty of Business and Management, 2010)
This research discusses about effect of the problem in cargo handling. They also were represented the solving for all the problem. It will include graph and report for all problem and then it will investigate and evaluate to solve the case. KLAS which means KL Airport Services. In cargo department we learn about the process of cargo handling. The purpose is to identify what kind of problem in handling cargo and also the way they solve. Cargo business it will affect in our economic. other than that, it will increase in the opportunity for citizen. In the air cargo there have process which include export and import process. KLAS cargo performance increase by monthly. The profit also getting more increase. Other than new airlines will coming to use KLAS services. The business become growth and will expand by next year because KLIA2 will opening soon. Lastly KLAS can become more progressive if they change their IT system and the place of cargo and also process for the handling cargo. It will change from the time means it will save time and it will reduce the mistake.